Chemical Characteristics of Fishball from Indian Mackerel and Oyster Mushroom with the Addition of Seaweed Porridge - Diana, Adella Farah; Rosida, Dedin Finatsiyatul; Kurnianto, Muhammad Alfid (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Fishball is a processed product made from fish meat, tapioca flour, and spices, which then undergoes grinding, mixing of the dough, molding, and boiling until fully cooked. Indian mackerel can enhance the nutritional value of fish balls because it contains high animal protein, while the addition of oyster mushrooms provides plant-based protein and fibre. Fishball also utilises seaweed as an additional hydrocolloid source, serving as a stabiliser and gelling agent that lends the fishball a chewy texture. The objective of this study was to determine the effect of different proportions of Indian mackerel and oyster mushrooms with the addition of seaweed porridge on the chemical characteristics of fishball. The research employed a Completely Randomized Design (CRD) with a two-factor factorial pattern and three replications, followed by analysis using ANOVA and DMRT at 5%. The first factor was the proportion of Indian mackerel and oyster mushrooms (90:10, 70:30, and 50:50). The second factor was the type of seaweed Eucheuma cottoni, Gracilaria sp., and Ulva lactuca. The best treatment was found in the proportion of Indian mackerel and oyster mushrooms (90:10) with the addition of Eucheuma cottoni seaweed porridge, which resulted in a composition of 73.11% moisture, 1.45% ash, 12.44% protein, 2.05% fat, and 10.94% carbohydrates. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero hungerSDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and Production